LeDiT – Learning with digital testimonies: Holocaust education 2.0 - Antonia Friebel; Christina Sanchez-Stockhammer (Societal Impacts)
The decline in knowledge about World War II and the Holocaust, coupled with increasing discrimination and populism, highlights the urgent need for innovative educational approaches. Abba Naor, a Jewish Holocaust survivor, has devoted his life to sharing his experiences, emphasizing the significance of historical learning to prevent future atrocities. The project ''Learning with digital testimonies'' (LeDiT) seeks to preserve Naor's memories and broaden their accessibility through interactive digital testimonies.Naor's interactive digital testimony offers an immersive and easily accessible means of engaging with a Holocaust survivor, vital for future generations who will not have the opportunity for in-person interactions. Originally recorded in German, the international version with English subtitles now allows users from around the world to ask a Holocaust survivor questions and learn about their personal stories. Implications of the project extend beyond educational settings in schools, with potential applications in museums, memorials, and online platforms dedicated to Holocaust education. Ongoing research aims to understand cross-cultural and generational perspectives on Holocaust education. Thus, interactive digital testimonies not only preserve the memories of survivors but also facilitate meaningful connections to historical events, fostering empathy and collective action against discrimination. Keywords 0Holocaust, memory, testimony, chatbot, Holocaust education, audiovisual translation, subtitling, interactive digital testimony